Value chain directionality, upgrading, and industrial policy in the Tanzanian textile and apparel sectors - Julian Boys; Antonio Andreoni (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
With recent changes in the global economy, policy makers are increasingly turning from global value chains to regional and national value chains as drivers of structural transformation in the global South. This paper examines economic and social upgrading in the Tanzanian textile and apparel sectors, with a particular focus on how outcomes vary across value chains, i.e. with value chain directionality. We also analyse industrial and trade policies at the national, regional, and global levels to see the extent to which they allocate rents that enable firms to capitalize strategically on the benefits offered by different value chain types. Data are drawn from fieldwork comprising a firm survey and semi-structured interviews with policy makers, as well as from official sources. We find that national, regional, and global value chains each offer distinct opportunities in terms of functional, product, process, and end-market upgrading as well as other economic and social outcomes and that while policy rents have been critical to the outcomes observed, there is scope to improve multi-scalar industrial policy design to achieve rapid structural transformation.
Keywords: O14; O25; L22; L67; 330; value chain directionality; upgrading; textiles; apparel; industrial policy; rents; Tanzania; SSA